Identifikasi Bakteriuria Asimtomaik pada Siswa SMA Kristen Passo Kota Ambon Tahun 2025 - Yulianti Ely (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The background of this study is bacteriuria, which is a cause of Urinary Tract Infections (UTIs). Bacteriuria indicates the growth of microorganisms in the urine, which is influenced by increased secretion of the hormone progesterone. This study aims to determine the characteristics of asymptomatic bacteriuria in Passo Christian High School students. The method used in this study is a descriptive method with a total sample of 25 students selected using a total sampling technique. The results showed that respondents were aged between 15 and 20 years, with 18 male respondents (72%) and 7 female respondents (28%). The results of urine culture and colony count examinations showed that 25 respondents (100%) had negative results, meaning that no bacteriuria was detected in these students. The conclusion of this study is that no indication of asymptomatic bacteriuria was found in Passo Christian High School students, indicating that in this sample, none of the students experienced urinary tract infections caused by bacteriuria.